Evaluasi Bantuan Ternak Sapi Bali di Kecamatan Mawasangka Kabupaten Buton Tengah - La Ode Muh Mpali; La Ode Arsad Sani; Hamdan Has (Zebra: Jurnal Ilmu Peternakan dan Ilmu Hewani, 2026)
Bali cattle have significant potential advantages and are sought after by breeders and farmers due to their adaptability to the environment and high productivity. The management of Bali cattle in Mawasangka District, through a local government program, is expected to foster awareness of efficient and optimal livestock farming. This study aims to analyze the input and output of the Bali cattle assistance program from the village government in Mawasangka District, Central Buton Regency. The method used in this study uses observation, interview, documentation and analyzed using descriptive analysis. The number of respondents used was 40 people. The research respondents were taken from two villages, namely Matara and Wasilomata villages. The results of this study indicate that the impact of village regulations on the management of Bali cattle assistance in Mawasangka District, Central Buton Regency : (1) The input process of the Bali cattle assistance program has been in accordance with the previously determined plan, namely 40 Bali cattle breeders and males. (2) Output (results) there was an increase in the number of livestock owned, an increase in the maintenance system and the number of pens owned increased.